2017
DOI: 10.1038/s41467-017-02214-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transgenesis and annotated genome sequence of the regenerative flatworm model Macrostomum lignano

Abstract: Regeneration-capable flatworms are informative research models to study the mechanisms of stem cell regulation, regeneration, and tissue patterning. However, the lack of transgenesis methods considerably hampers their wider use. Here we report development of a transgenesis method for Macrostomum lignano, a basal flatworm with excellent regeneration capacity. We demonstrate that microinjection of DNA constructs into fertilized one-cell stage eggs, followed by a low dose of irradiation, frequently results in ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
172
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 66 publications
(175 citation statements)
references
References 64 publications
2
172
1
Order By: Relevance
“…In addition, the previous study used a wild‐type strain which is not available anymore. The current study was performed with the inbred DV1 line, which was used for establishing the genome and transcriptome assemblies (Grudniewska et al., 2016; Wudarski et al., 2017). During the current survival studies, it was, however, shown that the DV1 line has a chromosome duplication, which has unknown effects on the biology of the worms (Wudarski et al., 2017; Zadesenets, Ershov, Berezikov & Rubtsov, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the previous study used a wild‐type strain which is not available anymore. The current study was performed with the inbred DV1 line, which was used for establishing the genome and transcriptome assemblies (Grudniewska et al., 2016; Wudarski et al., 2017). During the current survival studies, it was, however, shown that the DV1 line has a chromosome duplication, which has unknown effects on the biology of the worms (Wudarski et al., 2017; Zadesenets, Ershov, Berezikov & Rubtsov, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The current study was performed with the inbred DV1 line, which was used for establishing the genome and transcriptome assemblies (Grudniewska et al., 2016; Wudarski et al., 2017). During the current survival studies, it was, however, shown that the DV1 line has a chromosome duplication, which has unknown effects on the biology of the worms (Wudarski et al., 2017; Zadesenets, Ershov, Berezikov & Rubtsov, 2017). Another fascinating observation is that M. lignano does not show signs of a decreased regeneration capacity with advancing age, even after up to twelve amputations of the body, which is in strong contrast to mammals (Sharpless & DePinho, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The free‐living flatworm Macrostomum lignano Ladurner, Schärer, Salvenmoser, Rieger 2005 (Rhabditophora, Macrostomorpha) has emerged as a model for a broad range of research topics (Ladurner, Schärer, Salvenmoser, & Rieger, ), including the biology of aging (Mouton, Grudniewska, Glazenburg, Guryev, & Berezikov, ; Mouton et al, ), bioadhesion (Lengerer, Hennebert, Flammang, Salvenmoser, & Ladurner, ; Lengerer et al, ; Wunderer et al, ), regeneration (Egger, Ladurner, Nimeth, Gschwentner, & Rieger, ; Lengerer et al, ), stem cell biology (Grudniewska et al, ; Ladurner et al, ), and sexual selection (Marie‐Orleach, Janicke, Vizoso, David, & Schärer, ; Schärer, Littlewood, Waeschenbach, Yoshida, & Vizoso, ; Sekii et al, ). This research has led to the establishment of many resources and tools that are crucial for a modern genetic and genomic model, including in situ hybridization (Pfister et al, ), RNA interference (Kuales et al, ; Sekii et al, ), gene expression (Arbore et al, ; Grudniewska et al, ; Lengerer et al, ), genome and transcriptome assemblies (Wasik et al, ; Wudarski et al, ), transgenesis (Marie‐Orleach, Janicke, Vizoso, Eichmann, & Schärer, ; Wudarski et al, ), and a clarification of the phylogenetic context (Janssen et al, ; Schärer et al, ). Jointly, these achievements make M. lignano an excellent model to complement the, in several aspects, more established planarian flatworm models (Newmark & Sánchez Alvarado, ; Pellettieri & Sánchez Alvarado, ; Rink, ; Rouhana et al, ).…”
Section: Introductionmentioning
confidence: 99%